IMPLEMENTATION OF RELIGIOUS MODERATION VALUES IN SHARIA FINANCING TO SUPPORT THE GROWTH OF MSMES IN THE GLOBAL ERA - Afran; Muhammad Rasyad Al-fajar; Muhammad Zia Ulhaq (RADJA PUBLIKA, 2025)
One of the challenges faced in religious moderation is the extreme and harsh views of Islam, which force the views of other Islamic communities to use violence in doctrine. This can lead to a loose, unfocused understanding of Islam and the emergence of negative thoughts that follow cultures outside of Islam. So this study aims to determine the Implementation of Religious Moderation Values ​​​​in Sharia Financing to Encourage the Growth of MSMEs in the Global Era. This research will be conducted in Bima City, West Nusa Tenggara. This study uses Qualitative Research with a Case Study Approach. Data Collection Techniques, namely Observation, Interviews and Documentation. Data Analysis Techniques, namely Data Reduction, Data Presentation and Conclusion Drawing. Based on the results of the studyIt can be concluded that overall, sharia financing that applies the values ​​of religious moderation in Bima City can be a model for other regions in encouraging sustainable and inclusive MSME growth.